Geographic diversification, climate risk, and bank lending: Evidence from farm loans - Islam, Emdad; Singh, Mandeep (Journal of Financial Intermediation, 2025)
This study examines how geographically diversified banks adjust lending practices in response to abnormal hot temperatures, a proxy for climate risk, and finds that these banks reduce small farm lending by 2–3 percent more than geographically constrained banks after a standard deviation increase in abnormal temperatures. Geographically diversified banks demonstrate proactive portfolio risk management by prioritizing credit in core markets and reallocating funds away from high-risk non-core regions, leaving lending gaps in affected counties. These findings highlight the importance of geographic diversification in building climate resiliency for banks while reducing the total credit available to farmers in a region.